RSN earthquake report for 2016 - Porras, Juan L. (2017)
During 2016, the National Seismological Network (RSN: UCR-ICE) registered 4594 earthquakes and reported 210 felt events. There were 13 significant earthquakes with magnitude Mw > 5.0. The majority (86%) of felt earthquakes were shallow (< 30 km) and 93% had magnitudes (Mw) between 2.0 and 4.9. Local and regional faulting caused 68% of the felt earthquakes and the subduction of the Cocos Plate caused 30%. The geographic areas with the highest seismicity were the Guanacaste and Central volcanic ranges, Los Santos region, and an area to the southeast of the Nicoya peninsula. The highest intensity observed in Costa Rica during 2016 was VI+ (Modified Mercalli) due to the Capellades (5.5 Mw) and Bijagua earthquakes (5,4 Mw).